Inducing resistance of cucumber plants to diseases by using plant growth regulators - O. Onyshchenko; O. Chaiuk (Карантин і захист рослин)
Goal. To investigate the influence of plant growth regulators (PGR) and microfertilizer as plant resistance inducers for reducing the development of cucumber diseases in film greenhouses.